Factors Associated With the Occurrence and Evolution of Recent Small Subcortical Infarcts (RSSIs) in Different Locations - Hong, Hui; Zhang, Ruiting; Yu, Xinfeng; Jiaerken, Yeerfan; Wang, Shuyue; Luo, Xiao; Lou, Min; Huang, Peiyu; Zhang, Minming (Frontiers in Aging Neuroscience, 2020)
Recent small subcortical infarcts (RSSIs) can occur in different brain regions. Distinct etiologies might have been involved for RSSIs in different locations, and could further affect RSSIs cavitation and functional outcomes. In this study, we aimed to analyze the baseline clinical and imaging characteristics associated with the occurrence and cavitation of RSSIs in different locations. We retrospectively included patients who presented with RSSIs from a database for cerebral small vessel disease. Detailed information, including demographic, clinical, laboratory and radiological data were collected. We identified baseline RSSIs on diffusion weighted images, and divided them into brainstem, subcortical white matter and basal ganglia region groups. Cavitation was evaluated on follow-up T2 fluid-attenuated inversion recovery (FLAIR) images. Statistical analysis was performed to determine factors associated with the occurrence and cavitation of RSSIs in different locations. We found that patients with brainstem RSSIs had a higher proportion of diabetes (64.1%) compared to patients with subcortical white matter (27.3%, P<0.001) and basal ganglia region RSSIs (35.2%, P = 0.006), while patients with subcortical white matter RSSIs had higher white matter hyperintensity (WMH) burden compared to patients with basal ganglia region RSSIs (21.64 cm3 vs 11.10 cm3, P = 0.004). Follow-up analysis demonstrated that basal ganglia region RSSIs were less likely to cavitate than subcortical white matter RSSIs (61.4% vs 83.6%, P = 0.010), and contacting with WMH was associated with the cavitation of subcortical white matter RSSIs (OR: 101.760, P = 0.003). Our study demonstrated that RSSIs in different locations were associated with different clinical and imaging characteristics. Furthermore, cavitation of RSSIs might be affected by local lesion features and its surrounding environment, rather than general demographic and clinical factors.